The relationship between nature connectedness and happiness: a meta-analysis - Capaldi, Colin A.; Dopko, Raelyne L.; Zelenski, John M. (Frontiers in Psychology, 2014)
Research suggests that contact with nature can be beneficial, for example leading to improvements in mood, cognition, and health. A distinct but related idea is the personality construct of subjective nature connectedness, a stable individual difference in cognitive, affective, and experiential connection with the natural environment. Subjective nature connectedness is a strong predictor of pro-environmental attitudes and behaviours that may also be positively associated with subjective well-being. This meta-analysis was conducted to examine the relationship between nature connectedness and happiness. Based on 30 samples (n = 8,523), a fixed-effect meta-analysis found a small but significant effect size (r = .19). Those who are more connected to nature tended to experience more positive affect, vitality, and life satisfaction compared to those less connected to nature. Publication status, year, average age, and percentage of females in the sample were not significant moderators. Vitality had the strongest relationship with nature connectedness (r = .24), followed by positive affect (r = .22) and life satisfaction (r = .17). In terms of specific nature connectedness measures, associations were the strongest between happiness and inclusion of nature in self (r = .27), compared to nature relatedness (r = .18) and connectedness to nature (r = .18). This research highlights the importance of considering personality when examining the psychological benefits of nature. The results suggest that closer human-nature relationships do not have to come at the expense of happiness. Rather, this meta-analysis shows that being connected to nature and feeling happy are, in fact, connected.